Harmonising Global HigherEducation: Optimise Learning inthe New Normal (Comparative & International Education Series, 2022)
The COVID-19 pandemic has brought numerous challenges to global higher education, affecting students and educators. Most countries closed their higher learning institutions to protect students from the deadly disease. Although most institutions adopt remote learning as part of the solutions, many find it difficult to sustain quality education. Moreover, many students could not adopt remote learning due to the lack of internet connection, mainly in rural areas. Besides, learning from home has also led to various mental problems for students, such as anxiety, depression, and stress. Therefore, higher learning institutions, students, and educators must take practical measures to overcome the prevailing challenges. In the long term, they should leverage the renewed opportunities post-COVID-19 in lifting global higher education to the next level.How to cite in APA:Hu, M. K., & Kee. D. M. H. (2022). Harmonising global higher education: Optimise learning in the new normal. In E. J. Valeau, R. L. Raby, & U. Gaulee (eds), Shaping a humane world through global higher education: Pre-challenges and post-opportunities during a pandemic (pp. 131-140). STAR Scholars.